Monacha cartusiana (Gastropoda: Hygromiidae) in South Bohemia - Pavel Pech; Hana Pechová (Malacologica Bohemoslovaca, 2009)
The first record of non-indigenous expanding mollusc species Monacha cartusiana (O.F. Müller, 1774) is reported – the species was found on a dam of a coal-ash settling basin near České Budějovice.